Teaching resources for teaching energy conservation: systematic analysis (Research, Society and Development, 2022)
The objective of this work is to investigate the didactic resources available to Physics teachers about the teaching of energy conservation, through the methodology of systematic review. The results reveal that the type of teaching resource used most frequently in the classroom was experiments based on simulation technology.